Insights on the Mechanism of Manganese Oxide Precipitation from Mn2+ Solutions Using NaClO Under Highly Acidic Conditions, via Experimental Observations and Numerical Fitting of the Kinetic ODE System - Mauricio Córdova-Udaeta; Bowen Cheng; Shigeshi Fuchida; Yutaro Takaya; Keishi Oyama; Chiharu Tokoro (Journal of Chemical Engineering of Japan)
Manganese (Mn2+) oxidation is an important phenomena in environmental and industrial processes. This study aims to shed light on the mechanism by which NaClO oxidizes Mn2+ to precipitate MnO2 in the presence of HCl. Experiments at pH = 1.5 indicated that the autocatalytic formation and the BET surface area of the MnO2 precipitates are influenced by NaClO addition speed, while further tests suggested that highly acidic conditions may promote the redissolution of the initial MnO2 crystals formed after oxidant addition. Based on these observations, a completely novel kinetic mechanism for Mn2+ oxidation with NaClO in HCl solutions was proposed. Namely: the formation of MnO2 crystal nuclei by direct oxidation, the formation of an intermediary of the MnO2•HOCl type, and the disappearance of said intermediary, which can take two competing reaction pathways. The first pathway is thought to be the autocatalytic formation of MnO2 which ultimately precipitates, whereas the second one is proposed to be the redissolution of MnO2 back into Mn2+. To validate the proposed mechanism, the experimental setup was modeled as a semi batch reactor with pulsed NaClO addition, and the ensuing system of ordinary differential equations (ODEs) was solved numerically, yielding a reasonable fitting with experimental data.